Study protocol for the development of a European measure of best practice for people with long term mental health problems in institutional care (DEMoBinc) - Almeida, José Miguel Barros Caldas de (2009)
BMC Psychiatry Killaspy, Helen King, Michael Wright, Christine White, Sarah McCrone, Paul Kallert, Thomas Cervilla, Jorge Raboch, Jiri Onchev, Georgi Mezzina, Roberto Wiersma, Durk Kiejna, Andrzej Ploumpidis, Dimitris Caldas de Almeida, Jose MiguelSixth Framework of the European Commission The study is funded by the Sixth Framework of the European Commission authors gratefully acknowledge this support. The authors would to acknowledge the contributions of the members of the International Expert Panel throughout the study and thank them for their valuable Jerry Tew (social scientist, UK); social care-Mr Tony Ryan ( independent consultant on out of area placements, UK), Mr Michael Clark Improvement Partnership, UK); rehabilitation psychiatry - Professor Tom Craig ( UK), Dr Frank Holloway ( UK), Dr Weeghel ( Netherlands), Dr Joanna Meder ( Poland), Professor ( UK); service user perspective - Mr Maurice Arbuthnott (UK). Ms Vanessa Pinfold ( Rethink, UK); human rights law - Associate Professor Fernando Barrios-Flores ( University of Granada, Spain); mental - Professor Peter Bartlett ( Nottingham University, UK); disability - Ms Liz Sayce ( Royal Association for Disability and Rehabilitation, standards - Dr Geraldine Strathdee ( Healthcare Commission, UK) . 23 BIOMED CENTRAL LTD LONDON 471UM